Corrosion protection of carbon steel using zirconium oxide/silane pretreatment and powder coating - Chi, Nguyen Van; San, Pham Trung; Hang, To Thi Xuan; Nhung, Le Thi; Khoa, Truong Anh; Hoang, Nguyen; Hien, Nguyen Thu (Vietnam Journal of Science and Technology, 2019)
Surface pretreatment plays important role in improvement of corrosion resistance and adhesion of organic coatings. A new generation of metal pretreatments based on nanosize zirconium oxide or ogranosilane film has been investigated recently as an alternative method to phosphatation. In this paper, ZrO2/silane composite film on carbon steel was prepared and characterised by field emission scanning electron microscopy, energy dispersive X-ray spectrum and electrochemical measurements. The effect of ZrO2/silane surface treatment on the protection properties of powder coating was studied by salt spray test and adhesion measurement. The results obtained showed that ZrO2 was rapidly precipitated on the steel surface after first 1 minute immersion and ZrO2/silane film formed after 4 minutes immersion give best protective properties. Powder coating on carbon steel with ZrO2/silane pretreatement has equivalent protection performance like powder coating with phosphate pretreatment.